Hydrothermal Alteration and Ore Metal Mineralisation at Temon, Pacitan, East Jawa, Indonesia. - Sri Mulyaningsih; Yoyok Ragowo Siswomijoyo Sukisman; Radhitya Adzan Hidayah (Journal of Geoscience, Engineering, Environment, and Technology, 2021)
Pacitan area is known as Tertiary volcanic arc in Java, as the result of subduction zone of the Indian-Australian Plate beneath the Eurasian Plate since Oligocene. It was superimposed volcanism which formed a wide area of hydrothermal alteration zone, resulting potential ore metals mineralization, such at Temon and its vicinities, Pacitan Regency, East Java Province, Indonesia. The aim of study was to analyze hydrothermal alteration and ore metal mineralization zones. Method was surface mapping, thin section analyses, mineragraphic analyses and X-Ray Diffraction (XRD) analyses. Field study observed denuded and deformed volcanic crater geomorphology. There are ore placer deposits within the sand dunes of Grindulu River, which it consists of andesitic lava and breccia of Early Oligocene Mandalika Formation; Early Miocene lithic and vitric tuffs; and dacitic intrusion. The dikes of dacite as the last of volcanism was the host rock controlling the zonation of alteration and mineralization stages. Oblique normal faults and shear faults were cross over dilating formed fractures, which were as bodies to depositing the ore metals. There are (zone 1st) the argillic clay consists of quartz+alunite+dickite+kaolinite±illite with vuggy structures, (zone 2nd) the argillic clay consists of quartz+montmorillonite±illite zone with quartz vents, brecciated and sulfide massive, and (zone 3rd) as the chloritized zone with low grade and supergene on the edge of hydrothermal alteration. It was fluid overprinted that very acid to the core of zone 1st (pH2-4) into more netral pH 4-6 (zone 2nd) and (pH5-6) in the edge zone 3rd. The potentials ore metal mineralization are Fe and Cu by pyrite, chalcopyrite, hematite, and covellite. Other potential ore metal mineralization was also from enargite by the supergene alteration.